Social physical anxiety and nutritional attitude in athlete and non-athlete university students - Aktaş Üstün, Neslişah (Progress in Nutrition, 2020)
Study Objectives: The present study aimed to investigate the differences in the perception of social physique anxiety and nutritional attitudes of athletes and non-athlete university students. Besides, analyzing the correlations between the phenomena was another aim. Materials and Method: The study was designed as a cross-sectional quantitative study, and 375 university students from Hatay Mustafa Kemal University participated in the study. In analyzes of the data, independent samples t-test and Pearson Correlation analyzes were used. Results: This study showed that non-athlete participants reported significantly higher scores in physical appearance anxiety, fear of negative evaluation, and malnutrition sub-dimensions. On the other hand, athletes reported significantly higher scores on positive nutrition sub-dimension. Besides, malnutrition and social physique anxiety were positively correlated, and there were negative correlations between positive nutrition and social physique anxiety for both groups. Conclusion: Further research is still recommended to explore these associations in more depth.